Administracyjne kary pieniężne w ustawie o produktach kosmetycznych a dyrektywy wymiaru kary z art. 189d Kodeksu postępowania administracyjnego - Żywicka, Agnieszka; Wierzbowski, Marek (Studia Prawa Publicznego, 2022)
Within the legal system applicable in the Republic of Poland, it is the Act on cosmetic products of 4 October 2018 that regulates the supervision and supervisory measures in the market for such products. The domestic scheme of market supervision in respect of cosmetic products involves the competencies of the State Sanitary Inspectorate and the Trade Inspectorate. These bodies have been equipped with supervisory measures in the form of administrative sanctions, the most severe of which are financial administrative penalties imposed on business entities under their administrative criminal liability. The ratio legis of this legislative act is based on the premise that the appropriate level of protection of public interest (consumer health and life protection) may be best achieved through the preventive and repressive character of fines. The article substantiates the claim that effective supervision (which provides an appropriate level of consumer health and life protection) determines that supervisory bodies employ financial administrative penalties in judicial matters only if the directives on the penalty extent are understood correctly. This article constitutes a dogmatic and legal analysis of the statutory premises which determine the extent of financial administrative penalties imposed by supervisory bodies (the so-called ‘directives on the penalty extent’) on entrepreneurs within the cosmetics industry under the scheme stipulated in the Act on cosmetic products of 4 October 2018. The article aims to present how these premises are understood and applied in judicial matters by the State Sanitary Inspectorate and the Trade Inspectorate. It is the correct understanding and application of these premises (directives) for the extent of financial administrative penalties that result in the appropriate behaviour on the part of the entrepreneur during the course of the proceedings. This, in turn, is a direct consequence of the extent and severity of the administrative monetary penalty, as it has a preventive and repressive function.